Transplant outcomes using kidneys from high KDPI acute kidney injury donors. Issue 5 (31st March 2021) - Jadlowiec, Caroline C.; Hanna, Wael A.; Ninan, Jacob; Ryan, Margaret S.; Das, Devika M.; Smith, Maxwell; Khamash, Hasan; Mathur, Amit K.; Singer, Andrew; Moss, Adyr; Reddy, Kunam S.; Heilman, Raymond L.
Abstract: Kidney transplant (KT) outcomes from high kidney donor profile index (KDPI ≥85%) donors with acute kidney injury (AKI) remain underreported. KT from 172 high KDPI Acute Kidney Injury Network (AKIN) stage 0‐1 donors and 76 high KDPI AKIN stage 2‐3 donors from a single center were retrospectively assessed. The AKIN 2‐3 cohort had more delayed graft function (71% vs. 37%, p  < .001). At one year, there were no differences in the estimated glomerular filtration rate (44 ± 17 vs. 46 ± 18, p  = .42) or fibrosis on protocol biopsy (ci, p  = .85). Donor terminal creatinine ( p  = .59) and length of delayed graft function ( p  = .39) did not impact one‐year eGFR. There were more primary nonfunction (PNF) events in the high KDPI AKIN 2‐3 group (5.3% vs. 0.6%, p  = .02). With a median follow‐up of 3.8 years, one‐year death‐censored graft failure was 3.5% for AKIN 0‐1 and 14.5% for AKIN 2‐3 (HR 2.40, 95% CI 1.24‐4.63, p  = .01). Although AKIN stage 2‐3 high KDPI kidneys had comparable one‐year eGFR to AKIN stage 0‐1 high KDPI kidneys, there were more PNF occurrences and one‐year death‐censored graft survival was reduced. Given these findings, additional precautions should be undertaken when assessing and utilizing kidneys from severe AKI high KDPI donors.